Therapeutic drug monitoring of tacrolimus and mycophenolic acid in outpatient renal transplant recipients using a volumetric dried blood spot sampling device. (15th October 2018) - Zwart, Tom C.; Gokoel, Sumit R.M.; van der Boog, Paul J.M.; de Fijter, Johan W.; Kweekel, Dina M.; Swen, Jesse J.; Guchelaar, Henk‐Jan; Moes, Dirk Jan A.R.
Abstract : Aims: Tacrolimus and mycophenolic acid dosing after renal transplantation is individualized through therapeutic drug monitoring (TDM). Home‐based dried blood spot (DBS) sampling has the potential to replace conventional TDM sampling at the clinic. A liquid chromatography–tandem mass spectrometry (LC–MS/MS) assay was developed to quantify tacrolimus and mycophenolic acid in DBS and clinically validated for abbreviated area under the concentration–time curve (AUC) monitoring using an innovative volumetric DBS sampling device. Methods: Clinical validation was performed by direct comparison of paired DBS and whole blood (WB) (tacrolimus) and plasma (mycophenolic acid) concentrations and AUCs. Agreement was evaluated using Passing–Bablok regression, Bland–Altman analysis and DBS‐to‐WB predictive performance. TDM dosing recommendations based on both methods were compared to assess clinical impact. Results: Paired tacrolimus ( n = 200) and mycophenolic acid ( n = 192) DBS and WB samples were collected from 65 kidney(–pancreas) transplant recipients. Differences for tacrolimus and mycophenolic acid were within ±20% for 84.5% and 76.6% of concentrations and 90.5% and 90.7% of AUCs, respectively. Tacrolimus and mycophenolic acid dosing recommendation differences occurred on 44.4% and 4.7% of occasions. Tacrolimus DBS dosing recommendations were 0.35 ± 0.14 mg higher than for WB and 8 ± 3% of the initial dose. Mycophenolic acid DBS dosing recommendations were 23.3 ± 31.9 mg lower than for plasma and 2 ± 3.5% of the initial dose. Conclusions: Tacrolimus and mycophenolic acid TDM for outpatient renal transplant recipients, based on abbreviated AUC collected with a DBS sampling device, is comparable to conventional TDM based on WB sampling. Patient training and guidance on good blood‐spotting practices is essential to ensure method feasibility.